Property Development Strategy for a Townhouse Project in Bandung (Case Study: Setra Regency in Ciwaruga) - Iskandar, Delfiana Primashinta; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2013)
Requirement of resident in Bandung is increase progressively each year as the growth of industry of tourism also education that rapidly grow in Bandung that positively contributing to the growth of its density, the fact there was a gap between available housing and amount of families in Bandung, this condition becomes one of the interesting points for investors that very keen in capture business opportunity, the most important issue is increasing of middle class economy in Bandung that derives to the townhouse concept for residential development. Townhouse concept is an alternative to stay in the city besides apartments and real estate, Town house concept is rapidly growth in residential business because of its advantages. PT. XYZ is a company that is able to capture the business opportunities in this field, and they plan to develop a townhouse, but before the company executes the development of Setra Regency Townhouse project, feasibility study must be conducted because large sums are at stake in this project, also feasibility study can provide the best business strategy that will be most favorable for the company. After conducted market analysis, arise three alternatives of selling strategy, the company which acts as developer in this case should choose whether they should develop townhouse which each unit has big size, but the number of unit is only four units, or develop seven smaller units and the last alternative is to expand land area to built more houses. Feasibility study becomes a basis to determine the strategy that should be chose, the decision criteria is from shortest payback period, highest net present value, highest internal rate return, highest return on investment and the highest return on equity. From the feasibility study, the first alternative strategy will be the most favorable strategy with shortest payback period which is five months, highest IRR 84.91%; ROI and ROE 34.49%.Â Keyword : study feasibility, development strategy, selling strategy, Payback Period, NPV, IRR, ROI, ROE